EFEKTIVITAS MEDIA PEMBELAJARAN MATEMATIKA BERBASIS PERMAINAN EDUKATIF ULAR TANGGA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA DI ANGKOLA BARAT - Simbolon, Tara Mashuri; Ardiana, Nunik; Harahap, Muhammad Syahril (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2026)
The research conducted aims to determine the effectiveness of educational game-based mathematics learning media snakes and ladders to improve mathematical problem-solving skills of class X-2 students of SMA Negeri 1 Angkola Barat. The research method used in this study is using classical completeness. The subjects in this study came from 3 validators, as well as class X-2 students. The data collection technique used was using a questionnaire validation question and test for effectiveness testing. The results of the test question instrument validation analysis obtained a total percentage of achievement of 90% with the category